Application of Engineering Beverage Menu in Driving Guest Drink Purchase Decisions at Hotel Restaurants - Dolly Jamanda Putra; Lise Asnur; Hafiz Renaldi (Siber Journal of Advanced Multidisciplinary, 2026)
This research is motivated by the tendency of menu engineering studies that still place menus as managerial instruments to assess popularity, profitability, and sales contribution. In fact, in hotel restaurants, the drink menu also functions as a communication medium that helps guests read information, compare alternatives, and determine purchases. This study aims to analyze the influence of the application of the engineering beverage menu on the decision to purchase guest drinks at Wood 1820 Yuan Garden Restaurant, Hotel Pasar Baru, Jakarta. The study uses a quantitative approach with a causal associative design. The sample consisted of 99 guests who had bought a drink and were selected through purposive sampling. Data was collected using a Likert scale questionnaire containing 24 statements. The variables of the beverage engineering menu are measured through the display of the menu, clarity of information, product description, variety of drinks, placement of superior menus, price suitability, and ease of choice. Purchase decision variables are measured through product choice, belief in the restaurant, choice of place of purchase, time of purchase, and number of purchases. The data were analyzed using descriptive statistics, validity tests, reliability, regression prerequisite tests, and simple linear regression. The results showed that the implementation of the engineering beverage menu was in the good category with an average of 3,447, while the decision to purchase guest drinks was in the good category with an average of 3,464. The regression results showed a regression coefficient of 0.707, a significance of less than 0.001, and a determination coefficient of 0.439. These findings confirm that beverage engineering menus explain 43.90% of variation in purchasing decisions and act as a menu communication strategy that influences guest purchasing behavior.